Immigration and native welfare - Gabriel J. Felbermayr; Wilhelm Kohler (Johannes Kepler University of Linz, Department of Economics, 2004)
We unify two approaches towards identifying native welfare effects of immigration, one emphasizing the immigration surplus (Borjas, 1995,1999), the other identifying a welfare loss due to terms-of-trade effects (Davis & Weinstein, 2002). We decompose the native welfare effect of immigration into the standard complementarity effect, augmented by a Stolper-Samuelson effect, and a terms-of-trade effect. Using a structural model with three skill-classes we derive propositions on the wage and native welfare effects of various immigration scenarios. A calibration-based simulation reveals that the size of the inflow and immigrant income repatriation are key determinants of the welfare-ranking of different immigration scenarios.
Keywords: F22; F41; J31; 330; international migration; factor movements; international trade; non-tradable goods; welfare analysis; wages; general equilibrium; terms-of-trade; Einwanderung; Wohlfahrtsanalyse; Terms of Trade; Lohnniveau